A non-hydrostatic non-Boussinesq algorithm for free-surface ocean modelling. (December 2018) - Auclair, F.; Bordois, L.; Dossmann, Y.; Duhaut, T.; Paci, A.; Ulses, C.; Nguyen, C.
Highlights: An original time-split approach is implemented in a free-surface ocean model. NH flows are simulated in a natural way, propagating acoustic waves. The three-mode algorithm is detailed and its performances are evaluated. Acoustic, surface-gravity and internal-gravity waves are studied Abstract: A three-mode time-split algorithm is proposed to simulate non-hydrostatic ocean processes in a natural way: fast pressure adjustments via acoustic waves are explicitly represented. The full set of compressible Navier–Stokes equations is integrated for a free-surface ocean with three time-steps respectively associated to the internal, external and compressible (non Boussinesq) modes. The resulting three-mode algorithm can be implemented either in a fully compressible configuration or in a "pseudo-compressible" configuration by artificially lowering acoustic-wave velocities to reduce computational costs. The present description of the three-mode algorithm focuses in the first place on the simulation of non-hydrostatic processes in free-surface ocean models. Several test simulations related to linear and non-linear acoustic, surface and internal gravity waves are studied in details with the proposed three-mode algorithm.